Messenger RNA methylation regulates glioblastoma tumorigenesis - Dixit, Deobrat (Cancer Cell, 2017)
Messenger RNA modification provides an additional layer of gene regulation in cells. In this issue of Cancer Cell, Zhang et al. report that ALKBH5, a demethylase of the mRNA modification N(6)-methyladenosine, regulates proliferation and self-renewal of glioblastoma stem-like cells by modulating pre-mRNA stability and expression of the FOXM1 gene.